2012
DOI: 10.21059/buletinpeternak.v33i1.127
|View full text |Cite
|
Sign up to set email alerts
|

Estimasi Parameter Genetik Sifat Produksi Sapi Simmental di Balai Pembibitan Ternak Unggul Sapi Potong Padang Mengatas, Sumatera Barat (Estimation of Genetic Parameters of Production Characteristics on Simmental Cattle at Balai Pembibitan Ternak Unggulan

Abstract: INTISARIPenelitian ini bertujuan untuk mengestimasi parameter genetik sifat produksi, nilai pemuliaan (NP), hubungan rasio berat sapih (RBS) dengan nilai pemuliaan serta estimasi terhadap kemampuan berproduksi induk (MPPA) sapi Simmental yang dipelihara di Balai Pembibitan Ternak Unggul Sapi Potong Padang Mengatas. Data yang digunakan adalah recording berat lahir (BL), berat sapih (BS), pertambahan berat badan harian (PBBH) lepas sapih dan berat setahunan ( Dari 18 ekor pejantan, 10 ekor (55,56%) memiliki NP l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
2
Order By: Relevance
“…This showed that the selection of OG cattle based on these three traits (especially weaning weight) will produce quite high accuracy as well. The heritability estimate of birth weight in this study was lower than that of the result reported by Fathoni et al [13] for OG cattle in Kebumen Regency, namely 0.76 ± 0.12 and the results of research by Kaswati et al [14] in Bali cattle, namely 0.85 ± 0.44, the result reported by Karnaen [15] in Madura cattle, namely 0.33 ± 0.24, the result reported by Suhada et al [16] in Simental cattle, namely 0.11 ± 0.09 , the result reported by Estrada-León et al [17], namely 0.41 ± 0.09, and the research results of Putra et al ( 2014) [18] in Aceh cattle, namely 0.15 ± 0.13. The heritability value of birth weight of PO cattle as a result of this study is in agreement with the results of Lopez et al [19] research on Hanwoo cattle, which was 0.22 ± 0.02.…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…This showed that the selection of OG cattle based on these three traits (especially weaning weight) will produce quite high accuracy as well. The heritability estimate of birth weight in this study was lower than that of the result reported by Fathoni et al [13] for OG cattle in Kebumen Regency, namely 0.76 ± 0.12 and the results of research by Kaswati et al [14] in Bali cattle, namely 0.85 ± 0.44, the result reported by Karnaen [15] in Madura cattle, namely 0.33 ± 0.24, the result reported by Suhada et al [16] in Simental cattle, namely 0.11 ± 0.09 , the result reported by Estrada-León et al [17], namely 0.41 ± 0.09, and the research results of Putra et al ( 2014) [18] in Aceh cattle, namely 0.15 ± 0.13. The heritability value of birth weight of PO cattle as a result of this study is in agreement with the results of Lopez et al [19] research on Hanwoo cattle, which was 0.22 ± 0.02.…”
Section: Resultscontrasting
confidence: 81%
“…The heritability estimate of the weaning weight of this study was greater than that of Fathoni et al [13] in OG cattle, namely 0.36 ± 0.21, the results of Suhada et al [16] in Simental cattle, namely 0.39 ± 0.16, the results of Putra's research in Aceh cattle, namely 0.48 ± 0.58, and from the result of Estrada-León et al [17], namely 0.43 ± 0.09, but lower than the results of Karnaen [15] research in Madura cattle, namely 0.87 ± 0.45. The heritability estimate of the weaning weight of this study was not different form that of Lopez et al [19] result on Hanwoo cattle, which was 0.51 ± 0.03.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation